Abnormal Functional Connectivity Between Cerebral Hemispheres in Patients With High Myopia: A Resting FMRI Study Based on Voxel-Mirrored Homotopic Connectivity - Cheng, Yi; Chen, Xiao-Lin; Shi, Ling; Li, Si-Yu; Huang, Hui; Zhong, Pei-Pei; Wu, Xiao-Rong (Frontiers in Human Neuroscience, 2022)
Purpose: To study the changes of functional connections between the left and right hemispheres of HM patients and healthy controls (HCs) by resting functional magnetic resonance imaging (fMRI) based on voxel-mirrored homotopic connectivity(VMHC).To study the changes of resting state functional connectivity(rsFC) between the left and right hemispheres of HM patients and healthy controls (HCS) at rest by using resting functional magnetic resonance imaging (fMRI) based on voxel-mirror homotopy connectivity (VMHC). Patients and methods: 89 patients with HM (41 men, 48 women) and 59 healthy controls (24 men, 35 women) were collected and matched according to gender, age and education level. VMHC method was used to evaluate the changes of rsFC between cerebral hemispheres, and correlation analysis was carried out to understand the differences of brain functional activities between HM and HCs. Results: Compared with the HCs, the VMHC values of putamen and fusiform in the HM group were significantly lower (voxel-level p<0.01, Gaussian random field correction, cluster-level p<0.05). Conclusion: This study preliminarily confirmed the destruction of interhemispheric functional connection in some brain regions of HM patients, and provided effective information for clarifying the neural mechanism of HM patients.